EFEKTIVITAS PENGGUNAAN MEDIA BOX NUMERASI TERINTEGRASI DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS I SEKOLAH DASAR - Mardziyah, Farikhatul; Triyono, Ageng; Ratnaningsih, Arum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low numeracy skills of first-grade elementary school students and the suboptimal use of learning media in the teaching and learning process. This study aims to describe the implementation of numeracy box media integrated with deep learning and to determine its effectiveness in improving students' numeracy skills. This research uses an experimental method with a two-group pretest-posttest design. The research sample consisted of 26 students, with 13 students in the experimental class and 13 students in the control class. Data collection techniques used tests, interviews, and documentation. Data analysis techniques were analyzed using normality tests, homogeneity tests, and t-tests with SPSS assistance. The results of the first study showed that numeracy box media integrated with deep learning could be implemented properly and could improve students' numeracy skills. The second result showed the average pretest score of the experimental class was 69, increasing to 90 in the posttest. The hypothesis test results showed a significance value of 0.003 < 0.05, so Ha was accepted and H₀ was rejected. Thus, numeracy box media integrated with deep learning is effective in improving the numeracy skills of first-grade elementary school students.